EFEKTIVITAS PENGGUNAAN APLIKASI WATTPAD DALAM MENINGKATKAN KEMAMPUAN MENULIS CERPEN SISWA - Adriansyah Adriansyah; Fita Fatria (Universitas Asahan, 2025)
Short story writing is one of the essential language skills to be developed in Indonesian language learning. However, many students still face difficulties in writing creatively and structurally. This study aims to examine the effectiveness of using the Wattpad application to improve the short story writing skills of Grade XI IPS students at Madrasah Aliyah Al Washliyah Tebing Tinggi. The research employed a quantitative approach using a quasi-experimental design with a pretest-posttest control group. A total of 60 students were selected through purposive sampling and divided into two groups: the experimental group, which utilized Wattpad for writing activities, and the control group, which was taught using conventional methods. The main instrument was a short story writing test assessed based on six aspects: narrative structure, plot, character development, setting, language style, and originality. The results showed a significant difference in posttest scores between the two groups. The experimental group experienced a greater increase in scores, particularly in language style and originality. These findings indicate that Wattpad is an effective and innovative digital medium that enhances students' writing skills, fosters creativity, and provides a contextual writing experience aligned with students’ digital learning preferences.